Abdominal Fascia Suturing with Polypropylene Reduces intraabdominal Adhesion Incidence and Neutrophil, Macrophage, and Lymphocyte Infiltrations in Wistar Rats - Ketut Sudartana (Journal of Global Pharma Technology, 2016)
Background: Intraabdominal adhesion after surgery causes pain, infertility, and chronic abdominal pain. Intraabdominal adhesion also causes longer surgery time and increases intraoperative complications. This study aimed to prove that the use of polypropylene suture causes less intraabdominal adhesion and less inflammation compared to polyglycolic acid suture.  Methods: This was a randomized posttest-only control group study. Thirty-six mature male Wistar rats weighing 200-250 g were anesthetized with ketamine 50 mg/kg intramuscularly. It was incised on the inner abdominal wall layer by layer until peritoneum was seen. Wistar rats in Group A were sutured with polypropylene 4-0 with a half-centimeter apart. Rats in Group B were sutured with polyglycolic acid 4-0 suture. Peritoneum in both groups was not closed, and the abdomen was closed layer by layer, and then the lesion was enclosed with bandage. Relaparotomy was performed on day 14 and 30 to evaluate the presence of adhesion and inflammatory cells, MMP-1, TGF-ß, and TNF-α. Results: There was a significant difference between polypropylene-based sutures compared polyglycolic acid in terms of the presence of intraabdominal adhesion on 30 days after laparotomy (p=0.016). The infiltration of neutrophil, macrophage, and lymphocytes were significantly lower in polypropylene groups compared to polyglycolic acid (p<0.001). Conclusion: Polypropylene-based sutures resulted in less adhesion and inflammation compared to polyglycolic acid sutures in Wistar rats underwent laparatomy.Keywords: Laparotomy, Lymphocyte, Macrophage, Neutrophil, MMP-1.